Catalytic Effect of Two Shapes of Nano‐Fe2O3 on Hexanitrohexaazaisowurtzitane Using a Non‐Isothermal Decomposition Kinetic Method. Issue 5 (6th July 2016) - Gao, Rong; Zhao, Ningning; Liu, Jianbing; Zhang, Ting; Ma, Haixia
Abstract: Nanosized Fe2 O3 particles (nano‐Fe2 O3 ) with two shapes (tetrakaidecahedral and grainy) were synthesized by hydrothermal methods. The morphologies and structures were characterized using a combination of experimental techniques including X‐ray diffraction (XRD) and scanning electron microscopy (SEM). Two composites containing CL‐20 (hexanitrohexaazaisowurtzitane, HNIW) and tetrakaidecahedral nano‐Fe2 O3 [nmT‐Fe2 O3 /CL‐20] or grainy nano‐Fe2 O3 /CL‐20 (nmG‐Fe2 O3 /CL‐20) were prepared. The thermal behaviors of the two composites and pure CL‐20 were investigated using differential scanning calorimetry (DSC). Non‐isothermal decomposition kinetic parameters and the thermal decomposition mechanism of the two composites and CL‐20 were obtained. The apparent activation energy ( E a ) of the main thermal decomposition reaction of CL‐20, nmT‐Fe2 O3 /CL‐20 and nmG‐Fe2 O3 /CL‐20 are 181.94, 179.17, and 176.18 kJ mol −1, respectively. The thermal decomposition mechanism of CL‐20 as well as nmT‐Fe2 O3 /CL‐20 was controlled by the Avrami‐Erofeev equation ( n =2/5) assumed as random nucleation and subsequent growth, while, the reaction mechanism of the composite nmG‐Fe2 O3 /CL‐20 was controlled by the Mample Power law ( n =1/2). The reason for this difference may be due to the different morphology and particle size of the two nano‐Fe2 O3 particles. Abstract :